Five years experience in management of complicated infective endocarditis in a national reference center - Polo Lecca, Gracia del Carmen (2020)
Objective. To evaluate the epidemiological, clinical, echocardiographic, microbiological characteristics and complications of patients with complicated infective endocarditis (IE) in a Peruvian refence hospital. Material and methods. A retrospective, descriptive study was carried out reviewing the medical records of patients diagnosed with IE treated at Instituto Nacional Cardiovascular-INCOR between years 2012 and 2016; collecting clinical, imaging and laboratory variables. Results. 59 cases were included, predominantly males (66.1%) and the median age was 50 years (IQR 37-62). The most frequent comorbidities were congenital heart disease (42.3%) and the presence of a prosthetic valve (23.7%). The most frequent sign found in the physical examination was fever (69.49%) and the most common symptom was dyspnea (52.5%). The proportion of positive blood cultures was 55.9%, and in 51.5% of these the isolated pathogen was Staphylococcus spp. The most affected valve was the aortic (72.8%), the most frequent finding by echocardiography was the presence of vegetations (91.5%). The most common complications were atrioventricular block (28.8%) and heart failure (22%). Overall, in-hospital mortality was 20.3%. Conclusion. IE continues to be a challenging pathology, our clinical-epidemiological results are comparable to those found internationally, which reflect the change in the microbiology and in its epidemiology. However, despite advances in diagnosis and treatment, mortality remains unchanged.